Microplastics on the Menu: Plastics Pollute Indonesian Manta Ray and Whale Shark Feeding Grounds - Germanov, Elitza S.; Marshall, Andrea D.; Hendrawan, I. Gede; Admiraal, Ryan; Rohner, Christoph A.; Argeswara, Janis; Wulandari, Raka; Himawan, Mahardika R.; Loneragan, Neil R. (Frontiers in Marine Science, 2019)
The implications of plastic pollution, including microplastics, on marine ecosystems and species are increasingly seen as an environmental disaster. Yet few reports focus on filter-feeding megafauna in regions heavily impacted by plastic pollution, such as Indonesia in the Coral Triangle, a global marine biodiversity hotspot. Here, we evaluate plastic abundance and characterize debris from feeding grounds for manta rays (Mobula alfredi) and whale sharks (Rhincodon typus) in three coastal locations in Indonesia: Nusa Penida Marine Protected Area, Komodo National Park, and Pantai Bentar, East Java. A 200 µm plankton net was used to sample the top 0.5 m of the water column (‘trawl survey’) and floating plastics were assessed along ~ 440 m long transects (‘visual survey’) during the Indonesian north-west (‘wet’) and south-east (‘dry’) monsoon seasons during 2016 – 2018. Microplastics were identified visually, measured and categorized from trawl samples, and larger floating plastics were counted from vessels in visual transects. Plastic abundance ranged widely from 0.04 to 0.90 pieces m-3 (trawl survey) and 210 to 40,844 pieces km-2 (visual survey). Results from linear models showed significant seasonal and location differences in estimated plastic abundance for trawl and visual surveys in Nusa Penida and Komodo. Plastic abundance was up to ~ 44 times higher in the wet than the dry season, with the largest seasonal effect observed in Nusa Penida. Overall, small pieces < 5 mm (≥ 78%), films and fragments (> 50% combined) were the most prevalent plastics. Theoretical plastic ingestion rates were calculated using estimated filtration volumes of manta rays and whale sharks and the mean plastic abundance in their feeding grounds. Upper plastic ingestion estimates for manta rays were ~ 63 and 25 pieces h-1 for Nusa Penida and Komodo locations, respectively, and ~137 pieces h-1 for whale sharks in Java. Analysis of manta ray egested material confirmed plastic ingestion, the consequences of which might include exposure to toxic plastic additives and adhered persistent organic pollutants. Communicating this information to communities who stand to benefit from healthy megafauna populations might help local governments as they work towards reducing plastics in the marine environment.